Either/or - Batuman, Elif, 1977- (Penguin Press, 2022)
"From the acclaimed and bestselling author of The Idiot, the continuation of beloved protagonist Selin's quest for self-knowledge, as she travels abroad and tests the limits of her newfound adulthood. Selin is the luckiest person in her family: the only one who was born in America and got to go to Harvard. Now it's sophomore year, 1996, and Selin knows she has to make it count. The first order of business: to figure out the meaning of everything that happened over the summer. Why did Selin's elusive crush, Ivan, find her that job in the Hungarian countryside? What was up with all those other people in the Hungarian countryside? Why is Ivan's weird ex-girlfriend now trying to get in touch with Selin? On the plus side, it feels like the plot of an exciting novel. On the other hand, why do so many novels have crazy abandoned women in them? How does one live a life as interesting as a novel--a life worthy of becoming a novel--without becoming a crazy abandoned woman oneself? Guided by her literature syllabus and by her more worldly and confident peers, Selin reaches certain conclusions about the universal importance of parties, alcohol, and sex, and resolves to execute them in practice--no matter what the cost. Next on the list: international travel. Unfolding with the propulsive logic and intensity of youth, Either/Or is a landmark novel by one of our most brilliant writers. Hilarious, revelatory, and unforgettable, its gripping narrative will confront you with searching questions that persist long after the last page"--